Red sister eaudiobook - Lawrence, Mark (Book of the Ancestor, 2017)
From the international bestselling author of the Broken Empire Trilogy comes the first in a brilliant, breakout new fantasy series. A searing novel set in a brand new world, this series follows a young girl who enters a convent where girls are selected to train in religion, combat, or magic. Nona is selected to learn combat, and finds herself at the center of a epic battle for empire on the outer reaches of a dying universe.